Writing practices in continuing training of teachers that work in childwood education (Research, Society and Development, 2020)
It analyzes the role of writing practices in the continuing education of teachers working in early childhood education in the city of Vitória/ES. It is a collaborative research-action, which uses as a source 30 textual productions, elaborated by Physical Education, Arts and Classroom Teachers (Pedagogy) participating in a continuing education course. The tematic analysis, used to interpret the data, allows to group textual productions into three categories: writing as a teaching exercise (40.6%); forms of writing (bureaucratic and reflective) (33.4%); and writing as a formative option (26%). It is concluded that the continuing education, promoted in the articulation between university and school, contributed to the development of a qualified writing, able of enhancing the reflection / reframing of the pedagogical practice and the production of knowledge by the teachers.